Genomic Analysis Methods of Microorganisms - Canan Kebabçıoğlu; Osman Erganiş (Turkish Journal of Agriculture: Food Science and Technology)
Molecular approaches used to identify bacterial species use 16S rRNA and MLST to determine the genetic linkage of bacteria; MLST characterizes clonal linkages by examining differences in various gene loci. MLVA determines the genetic relationships of bacterial strains and biovar-level differences and assesses the copy number of repeated DNA sequences. Sequencing provides genetic data by identifying DNA sequences; Sanger sequencing is the basis for next-generation approaches. CRISPR modifies the genetic code and can correct mutations or control genes using Cas9. These methods are important for identifying bacterial species and annotating genomic information. The methods used for this purpose are brought together in this study. The explanation and detailed description of the methods examined will contribute to their use in the field of microbiology.